Foliar epidermal anatomy of some selected wild edible fruits of Pakistan using light microscopy and scanning electron microscopy. Issue 3 (12th November 2019) - Sadia, Haleema; Zafar, Muhammad; Ahmad, Mushtaq; Lubna,; Khan, Muhammad P. Z.; Yaseen, Ghulam; Ali, Muhammad I.; Sultana, Shazia; Kilic, Omer; Şahan, Zeynep; Alam, Naveed; Abbas, Qamar; et al.
Abstract: The present study is focused on the detailed foliar epidermal anatomy of some selected wild edible fruits (WEFs) from Pakistan using light microscopy (LM) and scanning electron microscopy (SEM). The studied species are Ficus racemosa L., Solanum nigrum L., Capparis spinosa L., Physalis divaricata D.Don, Rosa moschata Herrm. and Ribes orientale Desf. collected from various localities of Pakistan. The objective of the present study is to investigate qualitative and quantitative anatomical characters for the identification and differentiation of collected wild edible fruits. The characters studied are shape and size of epidermal cells, anticlinal wall pattern, trichome type and shape, average number of stomata, length and width of stomata and pore. The detailed microscopic investigation and variations in the characters recorded have a key role in the determination and authentication of wild edible fruits. This study possesses great potential for plant taxonomists to further evaluate the species at molecular and genetic levels. Abstract :